Complete nucleotide sequences of Nipah virus isolates from Malaysia - Chan, Y.P.; Chua, K.B.; Koh, C.L.; Lim, M.E.; Lam, S.K. (2001)
We have completely sequenced the genomes of two Nipah virus (NiV) isolates, one from the throat secretion and the other from the cerebrospinal fluid (CSF) of the sole surviving encephalitic patient with positive CSF virus isolation in Malaysia. The two genomes have 18246 nucleotides each and differ by only 4 nucleotides. The NiV genome is 12 nucleotides longer than the Hendra virus (HeV) genome and both genomes have identical leader and trailer sequence lengths and hexamer-phasing positions for all their genes. Both NiV and HeV are also very closely related with respect to their genomic end sequences, gene start and stop signals, P gene-editing signals and deduced amino acid sequences of nucleocapsid protein, phosphoprotein, matrix protein, fusion protein, glycoprotein and RNA polymerase. The existing evidence demonstrates a clear need for the creation of a new genus within the subfamily Paramyxovirinae to accommodate the close similarities between NiV and HeV and their significant differences from other members of the subfamily.